Analyzing Language Stylistics of Metaphors in “Lesson Learned” Album by Aziz Hedra: A Literary Study of Metaphors in Song Lyrics - Simanjuntak, Azzura Annisa; Adam, Adam; Dewi, Desi Surlitasari (Journal of Language and Literature Studies, 2026)
This study examines the metaphorical language style in Aziz Hedra's album "Lesson Learned" through the Conceptual Metaphor Theory as articulated by Lakoff and Johnson (1980), using the MIPVU as an analytical instrument in a qualitative descriptive methodology. The investigation focused on five carefully selected songs, from which forty-two distinct metaphorical expressions were extracted and systematically categorized according to ontological, structural, and orientational classifications. The findings indicate that ontological metaphors occupy a dominant position, conceptualizing emotional states as real entities and constructing a unified emotional trajectory that progresses from suffering to healing. The study ultimately argues that metaphors operate as fundamental cognitive mechanisms rather than merely decorative linguistic features, thus advancing the analysis of both cognitive linguistics and musicology through an increased understanding of emotional significance in lyrical compositions.